2021
DOI: 10.3390/su13179601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Indoor Air Pollution in Bhutanese Households during Winter: An Implication of Different Fuel Uses

Abstract: Measurements of indoor air pollution in Bhutanese households were conducted in winter with regards to the use of different fuels. These measurements were taken in Thimphu, Bhutan, for PM1, PM2.5, PM10, CO, temperature, air pressure and relative humidity in houses and offices with various fuels used for heaters and classified as the hospital, NEC, kerosene, LPG and firewood. The objective of this study was to measure the pollutant concentrations from different fuel uses and to understand their relationship to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…At the same time, Changchun's location in a bitterly cold region and the poor ventilation of homes in winter also contribute to high indoor pollution. (Kanabkaew, 2021).…”
Section: Analysis Of the Causes Of Urban Variability In Indoor Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, Changchun's location in a bitterly cold region and the poor ventilation of homes in winter also contribute to high indoor pollution. (Kanabkaew, 2021).…”
Section: Analysis Of the Causes Of Urban Variability In Indoor Pollutionmentioning
confidence: 99%
“…It was also found that indoor air pollution was more prevalent in classrooms with many students in the lower grades, taking into account the building layout (Abdel-Salam and Mahmoud, 2017). In some areas, fuel-based heaters are used for heating in winter, which undoubtedly aggravates indoor air pollution (Kanabkaew, 2021), and among the various types of fuel, firewood and kerosene contribute more to indoor PM2.5 (Isley et al, 2018). Similarly, outdoor air pollution contamination shows an upward trend during winter (Vladimíra, et al, 2021;Zhang, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Benzene is a genotoxic carcinogen, and no safe level is recommended according to the Agency for Toxic Substances and Disease Registry. 9 The legal limits of emissions and exposure to VOCs differ from nation to nation and usually rely on levels set by the Occupational Safety and Health Administration (OSHA). 10 IAP is relevant to health because people spend most of their time indoors.…”
Section: Noncooking Hrsmentioning
confidence: 99%
“…Their implications are further complicated, as most communities do not follow the exposure regulations set by the Occupational Health and Safety Administration (OSHA). 9,10 The Annual Health Bulletin states that acute respiratory disease (ARI) has been one of the top ten diseases in Bhutan over the last five years. 11 However, there is no or limited study assessing the correlation between air pollution and the occurrence of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%